The effects of online Team-Based Learning on undergraduate nursing students’ performance, attitudes and accountability during COVID-19 pandemic - Vannini, Valeria; Alberti, Sara; Epifani, Chiara; Valentini, Orietta; Ferri, Paola (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The COVID-19 pandemic forced many institutions to move Team-Based Learning to an online format. The primary aim of this study is to examine the performance of undergraduate nursing students on tRAT and iRAT during online TBL. The secondary aims are to evaluate the students’ attitudes and their accountability, preferences and satisfaction with online TBL.Methods: The study employed a one-group pretest-posttest quasi-experimental design. The primary outcome was evaluated by comparing the students’ average scores in the tRAT versus the iRAT in each online TBL session. The secondary outcomes were evaluated through the questionnaire designed by Parmelee et al. (2009) and the Team-Based Learning Student Assessment Instrument (TBL-SAI) (Mennenga, 2012).Results: A statistically significant improvement was identified between tRAT and iRAT performances in all online TBL sessions (p